Ministry of Petroleum and Mineral Resources Decree No. 166 Of The Year 2025 The selling price of one liter of benzene // Ministry of Petroleum and Mineral Resources Decree No. 167 Of The Year 2025 The selling price of one tone of mazut // Ministry of Petroleum and Mineral Resources Decree No. 168 Of The Year 2025 The sale price of natural gas = وزارة البترول والثروة المعدنية قرار رقم 166 لسنة 2025 سعر بيع اللتر من البنزين // وزارة البترول والثروة المعدنية قرار رقم 167 لسنة 2025 سعر بيع الطن من المازوت // وزارة البترول والثروة المعدنية قرار رقم 168 لسنة 2025 سعر بيع الغاز الطبيعى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.